Primate and Murine Type-C Viral Nucleic Acid Association Kinetics: Analysis of Model Systems and Natural Tissues - Scolnick, E. M. (1974)
Hybridization studies employing single-stranded (3)H-DNA transcripts of type-C viruses isolated from a woolly monkey or gibbon ape failed to detect nucleic acid sequences homologous to these viruses in the DNA from a variety of uninfected primate species. The possible significance of these results for the epidemiology of type-C viruses in primates is discussed.